Diagnostic and prognostic impact of mucin 1-6 expression in non-small cell lung cancer - William Sterlacci; Michael Fiegl; Lothar Veits; Alexandar Tzankov (Wolters Kluwer Medknow Publications, 2018)
Background: The prognostic significance and clinico-pathological characterization of mucin (MUC) expression in non-small cell lung cancer (NSCLC) is controversial and little studied. Aims: This study aims at elucidating this issue on the largest and most detailed cohort so far. Settings and Design: We examined the expression of MUC 1, 2, 4, 5AC and 6 on 371, well documented, surgically resected NSCLC cases. Materials and Methods: Immunohistochemical results were correlated with several of our previously studied, relevant parameters on this cohort including a follow-up period of up to 20 years. An additional point we examined for practical reasons that has not been addressed so far, was the possible assistance of MUC expression for the differentiation between a primary lung adenocarcinoma and metastasis from a known pancreatobiliary primary tumor. Statistical Analysis Used: Cronbach's Alpha reliability correlation, Spearman's correlation, ANOVA means of comparison with additional Kruskall-Wallis H-test, and Kaplan-Meier survival analysis were employed as statistical analyses in this study. Results and Conclusions: MUCs were associated with histologic subtypes, tumor differentiation and members of the epidermal growth factor receptor signaling pathway, although they were not found to be significant for prognosis. Expression of MUC1 correlated with certain other markers and may point to a group of patients relevant for upcoming treatment strategies involving MUC1. According to our findings, we also recommend additional MUC5AC staining for a thyroid transcription factor 1-negative adenocarinoma in the lung for the differentiation of a possible metastasis in the presence of a pancreatic ductal adenocarcinoma.